Study on the ability of Cyperus alternifolius for sludge treatment in constructed wetland - Thanh Phuong, Nguyen Thi; Phuoc, Nguyen Van (Vietnam Journal of Chemistry, 2014)
This research was focused on the ability of the Cyperus alternifolius plant to remove pollutant in sludge through the constructed wetland. The initial seeding sludge taken from the wastewater treatment plant of Vinh Loc industrial zone was treated by wetland at the increasing loading of 1.52 m3/m2.year, 3.04 m3/m2.year and 6.08 m3/m2.year in that order to adapt gradually and avoid loading shock. The treatment efficiency of pollutant concentration in model with plants was rather high with sludge loading rate of 3.04 m3/m2.year. The concentration of TOC, TP and TKN reduced 41 %, 40 % and 47 %, respectively. Besides, during the operation time, Cyperus alternifolius has adapted and well developed which is characterized by an increase in the biomass. In general, Cyperus alternifolius can treat industrial sludge with high efficiency. So that, this can open a new prospect in the future with planting of Cyperus alternifolius for sludge treatment and this also brings high economic efficiency. Keywords: Sludge treatment wetland, sludge dewatering, reed beds, sludge stabilization, Vertical-flow constructed wetlands.